Ewing sarcoma: A rare report from the Indian pediatric population - G, Dinesh Kumar; T, Dinesh; S Raj, Benita; Singh, Daniel Sundar (Indian Journal of Case Reports, 2024)
Ewing’s sarcomas are rare, aggressive tumors with a tendency toward recurrence following resection, and early metastasis. Although patients of younger or older age account for almost 30% of instances, peak incidences occur between the ages of 10 and 20. We, hereby, report the case of a 10-year-old girl who presented with a 3-month history of pain in her right hip that was unable to be relieved by non-steroidal anti-inflammatory medicine and physical therapy. On examination, bone marrow aspiration revealed that the infiltration of malignant small round blue cells was managed by anticancer therapy successfully.